Artemia sp. na alimentação de larvas de jundiá (Rhamdia quelen) - Diemer, Odair [UNESP]; Neu, Dacley Hertes; Sary, Cesar; Finkler, Joana Karin; Boscolo, Wilson Rogério; Feiden, Aldi (FapUNIFESP (SciELO), 2012)
A considerable problem in the catfish larvae rearing is related to the first feeding. This study aimed to determine the larvae growth and the survival of silver catfish submitted to feeding with Artemia sp. in different time periods. The study was conducted in the Aquaculture Laboratory of the Universidade Estadual do Oeste do Paraná, with four treatments and five replications, constituted by feeding with Artemia sp. in 5, 10, 15 and 20 days, and after each period of time, by its replacement by ration. We used 200 larvae distributed into 20 aquariums, soon after the eggs hatched. The larvae were fed 4 times a day until apparent satiation for 30 days. The Artemia sp. feeding for 15 days provided the best results on weight gain, final length and survival.
Artemia sp in feeding larvae of silver catfish (Rhamdia quelen)
Keywords: Aquaculture; Iguaçu river; Native fish; Nutrition; Artemia; Artemia sp.; Rhamdia quelen